Gender-Related Differences in Chest Pain Syndromes in the Frontiers in CV Medicine Special Issue: Sex & Gender in CV Medicine - Mehta, Puja K.; Wei, Janet; Shufelt, Chrisandra; Quesada, Odayme; Shaw, Leslee; Bairey Merz, C. Noel (Frontiers in Cardiovascular Medicine, 2021)
Coronary artery disease (CAD) is the leading cause of morbidity and mortality among both women and men, yet women continue to have delays in diagnosis and treatment. The lack of recognition of sex-specific biological and socio-cultural gender-related differences in chest pain presentation of CAD may, in part, explain these disparities. Sex and gender differences in pain mechanisms including psychological susceptibility, the autonomic nervous system (ANS) reactivity, and visceral innervation likely contribute to chest pain differences. CAD risk scores and typical/atypical angina characterization no longer appear relevant and should not be used in women and men. Women more often have ischemia with no obstructive CAD (INOCA) and myocardial infarction, contributing to diagnostic and therapeutic equipoise. Existing knowledge demonstrates that chest pain often does not relate to obstructive CAD, suggesting a more thoughtful approach to percutaneous coronary intervention (PCI) and medical therapy for chest pain in stable obstructive CAD. Emerging knowledge regarding the central and ANS and visceral pain processing in patients with and without angina offers explanatory mechanisms for chest pain and should be investigated with interdisciplinary teams of cardiologists, neuroscientists, bio-behavioral experts, and pain specialists. Improved understanding of sex and gender differences in chest pain, including biological pathways as well as sociocultural contributions, is needed to improve clinical care in both women and men.